Lack of additive benefit of oral steroids on short‐term postoperative outcomes in nasal polyposis. (22nd November 2019) - Arancibia, Claudio; Langdon, Cristóbal; Mullol, Joaquim; Alobid, Isam
Abstract : Objectives: There is a lack of evidence concerning the efficacy of oral corticosteroids (OCS) as a postoperative treatment for patients with chronic rhinosinusitis with nasal polyps (CRSwNP). The objective of our study was to determine the short‐term additive benefit of postoperative OCS in CRSwNP patients. Methods: We prospectively randomized CRSwNP patients who were treated by endoscopic sinus surgery. All patients were resistant to maximum medical treatment according to European position paper on rhinosinusitis and nasal polyps 2012 guidelines. Treatment group received postoperative OCS in descending doses plus nasal douching over a period of 4 weeks, whereas the control group received only nasal douching. The efficacy of OCS was determined by a total 5 item symptoms score (T5SS), polyp size score, Barcelona Smell Test 24 and Medical Outcome Study Short Form‐36 questionnaire for quality of life (QoL). Results: Of the 70 enrolled patients, 35 were in the treatment group and 35 in the control group. After 4 weeks of follow‐up, patients from both groups improved in T5SS, QoL, endoscopic findings (except for crusts that increased in both) and sense of smell, without significant differences between OCS and control groups. Conclusion: Postoperative OCS as an add‐on treatment for CRSwNP patients does not improve sinonasal and QoL outcomes; thus, they should not be routinely recommended. Level of Evidence: Ib Laryngoscope, 2019